การวิเคราะห์ต้นทุน-อรรถประโยชน์ของการปลูกถ่ายไขกระดูกเปรียบเทียบกับการรักษาด้วยเคมีบำบัดในผู้ป่วยมะเร็งเม็ดเลือดขาวมัยอีลอยด์ชนิดเฉียบพลัน ผู้ใหญ่ ณ โรงพยาบาลจุฬาลงกรณ์ - สุรีรัตน์ งามเกียรติไพศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of the study was to compare the cost-utilities between bone marrow transplantation (BMT) and chemotherapy (CT) for the treatments of adult patient with acute myeloid leukemia (AML) at King Chulalongkorn Memorial Hospital (KCMH). This retrospective-prospective cohort study was conducted the utility data during the period of October 2005 to March 2007. This provider-perspective costing was collected available data between October 1994 and March 2007. The first of the two components of costs was medical care cost (MCC). MCCs consisted of general drugs, chemotherapeutic drugs, medical supplies, laboratory tests, radiological investigations and radiotherapies, and blood or blood components. MCCs were determined by reviewing the medical records. The second component of costs was routine service cost (RSC). RSC composing of labor cost, general material cost, capital cost, and indirect cost were adjusted from the research and reports of annual cost analysis of KCMH since 2001. All costs were converted to 2006 values using the Thai consumer price indices. The utility data was obtained from quality-of-life interview by EQ-5D questionnaire during October 2005 to March 2007. The data of both group were analysed to the annual cost per person and were synthesized the Markov models and then ran cohort simulation in order to project the life-year costs. The study found that average-annual costs of BMT in complete remission (CR) was ฿651,081 per person and this in relapse was ฿507,815 per person. The average-annual costs of CT in CR and relapse were ฿489,286 and ฿428,892 per person, respectively. The utility units of BMT in CR and in relapse were 0.7348 and 0.4120, respectively. The CT group had 0.5172 and 0.2926 of utility units in CR and relapse, respectively. The expected life-year costs by 3 %discounting were ฿2,392,778 and ฿2,217,405 in BMT and CT, respectively (฿175,373 of difference). AML patients with BMT gained 2.1634 QALY. AML patients with CT gained 1.8363 QALY. The QALY differences between BMT and CT were 0.7359. As a result, the costs of BMT and CT were 1,098,196 and 1,242,971 per QALY (฿150,565 of difference). From the Markov models, the probabilities of 5-year survival an overall survival in BMT were 0.1573 and 0.2458, respectively. These were 0.2024 and 0.3508 in CT. By sensitivity analysis, interestingly, cost per QALY of BMT decreased in the conditions of first remission and the patients that were younger than 35 or in the conditions of first remission and the patients that did not have any comorbidity or complication. These findings indicate that BMT is more worth than CT. Thus, Thai healthcare delivery system should inform rational choices to the patients and their communities for co-decision. Moreover, the system should be administrated for comprehensive efficiency by using the evidence-based data, not for exclusive reduction the overall budgets.